TANGGUNG JAWAB PUSAT PELAYANAN TERPADU PERLINDUNGAN PEREMPUAN DAN ANAK TERHADAP ANAK KORBAN KEKERASAN DALAM RUMAH TANGGA - maharani, virgi aprilian; hasuri, hasuri (Universitas Gorontalo, 2024)
Child protection is an effort to protect children so that they can carry out their rights and obligations. The formation of P2TP2A is a form of government responsibility to provide protection for women and children from violence, P2TP2A is an embodiment of integrated services between the Government and the community in providing protection for victims. The discussion in this research is the responsibility of P2TP2A towards child victims of domestic violence, namely the efforts or services provided by the P2TP2A institution to child victims to provide protection. The conclusion from this research is that there are several types of services provided by P2TP2A, namely in the form of prevention, treatment and empowerment for victims who experience violence. Then the types of services provided by P2TP2A are One-Stop Services and Network Services. Then other services provided are in the form of settlement processes through litigation and non-litigation. These include Legal Services, Medical Services and Psychological Services. Mechanisms for Handling Victims and Providing Assistance to Victims by P2TP2A Serang City, namely Receiving Victims, Outreach, Referral, Registration and Identification.Â